Designing educational activities based on interactive chat in family education decision and measuring its impact on the school achievement in the second grade students in Taif - Alrasheed, Sawsan Saad (Journal of Curriculum and Teaching Methodology, 2022)
The current study targeted the design of educational activities based on interactive chatting in family education decision and measuring its impact on the secondary grade students in Taif. The study sample of (60) students. The tribal and satellite testing tool was used to collect data and analyzed responses using the statistical package of social science (SPSS). The results of the study revealed statistically at the level of ≥α)0.05) levels between the graduates of the experimental and control groups in favor of experimental group students in the recall level, the level of understanding, the level of application, and the total degree is attributed to the effectiveness of interactive chat activities. The study recommended the importance of adopting learning activities based on interactive chatting for the development of academic achievement or scientific concepts, and the rehabilitation of the functions for its design and implementation.
Keywords: educational activities; interactive chat; school achievement